Evidence‐based weight loss interventions: Individualized treatment options to maximize patient outcomes. Issue 1 (24th November 2020) - Bray, George A.; Ryan, Donna H.
Abstract: Against the backdrop of obesity as a major public health problem, we examined three questions: How much weight loss is needed to benefit patients with obesity? How well do current therapies do in producing weight loss? What strategies can be used to improve patient outcomes using evidence‐based studies. This paper reviews literature on the outcomes of lifestyle, diet, medications and surgical treatments for obesity using literature searches for obesity treatments. Current treatments, including lifestyle, diet and exercise, produce a weight loss of 5% to 7% on average. Despite continued attempts to identify superior dietary approaches, most careful comparisons find that low carbohydrate diets are not significantly better than low fat diets for weight loss. The four medications currently approved by the US Food and Drug Administration for long‐term management of obesity are not as effective as surgery, adding about 5% on average to lifestyle approaches to weight loss. Two new medications that are under investigation, semaglutide and tirzepatide, significantly improve on this. For all treatments for weight loss, including lifestyle, medications and surgery, there is enormous variability in the amount of weight lost. Examination of this literature has yielded evidence supporting baseline and process predictors, but the effect sizes associated with these predictors are small and there are no prospective studies showing that a personalized approach based on genotype or phenotype will yield uniform success. Because obesity is a chronic disease it requires a 'continuous treatment model' across the lifespan.